FAITH MEETS TECHNOLOGY: NAVIGATING STUDENT SATISFACTION IN INDONESIA’S ISLAMIC HIGHER EDUCATION ONLINE LEARNING - Tanti, Tanti; Anwar, Kasful; Jamaluddin, Jamaluddin; Saleh, Ahmad Syukri; Yusup, Deni Kamaluddin; Jahanifar, Mojtaba (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2025)
As the digital revolution continues to redefine global education, Islamic Higher Education (IHE) institutions in Indonesia face the dual challenge of integrating modern technology with traditional religious instruction. This study explores how digital learning environments can harmonize with Islamic pedagogical values to shape student satisfaction in online learning. Guided by Albert Bandura’s social cognitive theory, this research investigates the psychosocial and contextual factors influencing satisfaction and perceived learning outcomes among students in faith-based online education. A total of 3,270 undergraduate students from four IHE institutions participated in this study. Using Structural Equation Modeling-Partial Least Squares (SEM-PLS), we developed a novel integrative model that incorporates conventional online learning dimensions—such as teacher support, content adaptability, student interaction, and perceived ease of use—alongside embedded Islamic values. The analysis reveals that Islamic values are the most dominant factor influencing student satisfaction, surpassing even technological usability. Teacher support significantly enhances metacognitive skills, reinforces faith-based values, and increases overall satisfaction. Additionally, the availability of virtual laboratory resources and adaptive content was found to moderate the relationship between psychosocial factors and learning outcomes. This research contributes a faith-integrated theoretical framework for understanding online learning in religious educational settings, a relatively underexplored domain. It explains 72.8% of the variance in student satisfaction, offering robust insights for curriculum designers, educators, and policymakers aiming to optimize Islamic online education. The study opens new pathways for cross-cultural research at the intersection of technology, pedagogy, and religious values in digital learning environments.